APPLICATION OF CRM-SYSTEMS IN THE WORK OF RETAIL FRANCHISE NETWORKS - Smirnova, Elena; Kuznetsova, Elena; Dianov, Dmitry; Tolmachev, Oleg (Revista Inclusiones, 2020)
In this article, CMR-systems as a tool for increasing the efficiency of a company’s interaction with clients are characterized. The essence of CRM-systems and the role of their implementation at an enterprise are determined. The main functions and benefits of using CRM are defined. Based on an expert survey, the authors of the article consider the essence of the concepts of CRM-system and CRM-strategy and define the main directions of the CRM-strategy in relationship management of franchisor and franchisee in a retail franchise network, as well as the main goals of using CRMsystems in retail franchise networks. The authors present the correlation between the use of new technologies and opportunities to improve relationship management in retail franchise networks. The specialized software for the CRM-system functioning, the main stages of the CRM-strategy implementation in a retail franchise network’s activity, and the main advantages and disadvantages of the CRM-systems use in a retail franchise network’s activity are defined.